Analysis of Indonesian Digital Teaching Books with National Insight for Students in Islamic Religious College - Alfiati; Suwandi, Sarwiji; Andayani; Setiawan, Budhi (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
This study aims to examine the condition of books and the need for digital textbooks for lecturers and students of Islamic Higher Education in the Madiun area which consists of six universities, namely the Islamic High School (STAI) Madiun, STAINU Madiun, STAI Ma'arif Magetan, IAIN Ponorogo. , IAI Ngawi, and Insuri Ponorogo. The method used at this stage is exploratory qualitative. The aim is to provide an overview of the textbooks used for teaching so far. The activity carried out is to analyze the feasibility of textbooks used to teach so far and the need for digital textbooks for lecturers and students of Islamic Higher Education in the Madiun area. The tools used for the preliminary study include a questionnaire for students, a list of interview questions for Indonesian language lecturers, and a study format for Indonesian language textbooks. Questionnaires were given to students of Islamic Higher Education in five residency universities of Madiun to find out students' needs for Indonesian language textbooks. In addition, the researcher also interviewed Indonesian language lecturers to find out the lecturers' perceptions of the Indonesian language textbooks used through a list of questions that had been compiled by the researchers. Furthermore, the researcher used the textbook review format to examine the Indonesian MKDU textbooks from the aspect of national insight. Based on the results of observations that have been carried out at six Islamic Universities in the Residency of Madiun, it is found that; (1) learning scientific writing is very important to be taught in universities because every student should have the ability to write scientifically as a provision in preparing scientific papers, (2) students still have not mastered correctly in writing scientific papers, (3) there are no language textbooks Indonesia makes it difficult for students to find references related to scientific writing material, (4) lecturers and students need books to support